Fungal endophytes in leaves, twigs and bark of Quercus ilex from Central Spain - Collado, J.; Platas, G.; Pelaez, F. (NOVA HEDWIGIA, 1996)
Fungal endophytes were isolated from leaves, twigs and bark discs of the main stem of 16 individuals of Quercus ilex at two sites in the forests of El Pardo, Madrid, central Spain. From 512 segments of each sample type, 1084 fungal isolates were obtained, distributed among 98 species of filamentous fungi, yielding about 21 species/tree. Four isolation media were tested, which showed different behaviour depending on the type of sample. The use of fungitoxic compounds, such as benomyl or cycloheximide, resulted in a decrease in the number of isolates and species recovered, especially from leaves. Most of the dominant fungal species were not isolated from the four media indistinctly, but were preferentially recovered from one of the media. Twigs exhibited a higher degree of fungal infection than bark discs and leaves. The mycota isolated from bark and twigs were more similar to each other than to the fungal populations recovered from leaves. The frequency of isolation of most of the dominant fungal species depended significantly upon the sample type. A Phoma sp. was the only taxon similarly distributed among the three sample types. The height from which the bark discs were removed also influenced the population recovered. Both sampling sites were similar with respect to the number of species recovered from twigs and bark discs, but differed in the number of species from leaves. As in other plant and non-plant fungal communities, the population recovered from Q. ilex was characterized by a few species which accounted for most of the isolates, and a much larger number of species present with low frequencies. Five species (Nodulisporium sp., Acremonium strictum and three Phoma-like coelomycetes) represented more than 50% of the whole isolates. Coelomycetous anamorphs of ascomycetes bearing small, hyaline ameroconidia, were the most abundant group of fungi, whereas teleomorphs were rarely seen.
The following values have no corresponding Zotero field: pub-location: JOHANNESSTR 3A, D-70176 STUTTGART, GERMANY publisher: GEBRUDER BORNTRAEGER
Keywords: endophytes; isolation; microbial diversity; Quercus ilex